Seasonal variability in irradiance affects herbicide toxicity to the marine flagellate Dunaliella tertiolecta - Sjollema, Sascha B.; Vavourakis, Charlotte D.; van der Geest, Harm G.; Vethaak, A. Dick; Admiraal, Wim (Frontiers in Marine Science, 2014)
Photosynthetically Active Radiation (PAR) and Ultraviolet Radiation (UVR) of the solar spectrum affect microalgae directly and modify the toxicity of phytotoxic compounds present in water. As a consequence seasonal variable PAR and UVR levels are likely to modulate the toxic pressure of contaminants in the field. Therefore the present study aimed to determine the toxicity of two model contaminants, the herbicides diuron and Irgarol®1051, under simulated irradiance conditions mimicking different seasons. Irradiance conditions of spring and autumn were simulated with a set of Light Emitting Diodes (LEDs). Toxicity of both herbicides was measured individually and in a mixture by determining the inhibition of photosystem II efficiency (ΦPSII) of the marine flagellate Dunaliella teriolecta using Pulse Amplitude Modulation (PAM) fluorometry. Toxicity of the single herbicides was higher under simulated spring irradiance than under autumn irradiance and this effect was also observed for mixtures of the herbicides. This irradiance dependent toxicity indicates that herbicide toxicity in the field is seasonally variable. Consequently toxicity tests under standard light conditions may overestimate or underestimate the toxic effect of phytotoxic compounds.